Reproductive and fetal toxicity studies of histamine H3 receptor antagonist DL76 used in mice to prevent maximal electroshock-induced seizure - Bastaki, Salim M.; Abdulrazzaq, Yousef M.; Zidan, Marwan Abdelrahim; Shafiullah, Mohamed; Alaryani, Saif Ghdayer; Alnuaimi, Fatima Awad; Adeghate, Ernest; Mohsin, Sahar; Akour, Amal; Siwek, Agata; Łażewska, Dorota; Kieć-Kononowicz, Katarzyna; et al. (Frontiers in Pharmacology, 2024)
Research during the last two decades has provided more information concerning anticonvulsant activities of histamine H3 receptor (H3R) antagonists in animal epilepsy models. Therefore, the in vivo anticonvulsant effect of the H3R antagonist DL76 against maximal electroshock (MES)-induced seizures in mice having valproic acid (VPA) as a reference antiepileptic drug (AED) was assessed. DL76 is a histamine H3 receptor (H3R) antagonist with proven high in vitro affinity, in vitro selectivity profile, and high in vivo antagonist potency in mice. In addition, DL76 was tested for its reproductive and fetal toxicity in the same animal species. Our observations showed that acute systemic administration (intraperitoneal; i.p.) of DL76 (7.5, 15, 30, and 60 mg/kg, i.p.) provided a significant and dose-dependent protection in female as well as male mice against MES-induced seizures. Moreover, The DL76-provided protective effects were comparable to those offered by the VPA and were reversed when animals were co-administered with the CNS-penetrant selective H3R agonist R-(α)-methylhistamine (RAM, 10 mg/kg, i.p.). Moreover, the administration of single (7.5, 15, 30, or 60 mg/kg, i.p.) or multiple doses (3 x 15 mg/kg, i.p.) of H3R antagonist DL76 on gestation day (GD) 8 or 13 failed to affect the maternal body weight of mice when compared with the control mice group. Also, no significant alterations were detected in the average number of implantations and resorptions between the control and DL76-treated groups at the early stages of gestation and the organogenesis period. In addition, no significant differences in the occurrence of skeletal abnormalities, urogenital abnormalities, exencephaly, exomphalos, facial clefts and caudal malformations were observed. The significant abnormalities witnessed in the treated groups of mice were only in the length of long bones and body weight. In conclusion, the novel H3R antagonist DL76 protected test animals against MES-induced seizures and had a low incidence of reproductive and fetal malformation with de-creased long bone lengths in vivo and showed an acceptable safety profile in vivo, signifying the potential future therapeutic value of H3R antagonist DL76 for future preclinical as well as clinical developments to be clinically used in the management of epilepsy.